CCTV BERBASIS WEB SEBAGAI SISTEM KEAMANAN - Agung, I Putu Suhada (Institut Seni Indoensia Surakarta, 2009)
Experiment research about CCTV under web for security system, is made to design a prototype remote security system. This security system can be develope for remote security system that can be accessedfrom intranet and internet networks. Streaming is an effective methode to send big capacity files like audio and video from intranet or internet networks. The benefitfor using streaming is a very big capacity offile(s) can be shown has no need all parts offile(s) be accessed. Ussually streaming proccess (Windows Media, Real Media, Quicktime and Flash) pass through a crucial phases and need very long time process. Else ussually streaming format needs much bandwidth and very large saving media. Unreal Streaming Server is an under windows streaming software, that has more function like online (live) features and offline (on demand) steraming than old different St reaming software. Unreal Streaming Server is the right choice for developed as CCTV under web for security system. This software needs only 1 Giga Byte / 1 GB to record online/live seasson as long as 1 month. Unreal Streaming Server no needs decode an originalfile that will be used; all offile is streamed as an originalfile format. Player can receive stream, if codec is installed on. Security level can be set from server with security choices like : password, authent fi cation, session and blocking acccess. Other main facility is CCTVstream can be access from cellular phone (celiphone) that has Windows OIS, Symbian 0/S or Java that can be accessed everywhere. Keywords: CCT1 Streaming, Unreal Streaming Server